Communicatio idiomatum w wybranych pieśniach wielkopostnych - Strzelczyk, Grzegorz (Studia Pastoralne, 2026)
The article presents an analysis of the expressions according to communicatio idiomatum in the texts of the Lenten songs contained in the Liturgical Songbook ‘Niepojęta Trójco’ (‘Mysterious Trinity’) (vol. 1) published by the Dominican Liturgical Centre. Expressions of this kind appear in about 1/3 of the songs and almost all of them have a descending character (properties, states, typically human activities are attributed to the subject identified by the name or the title referring to divinity). It does not seem that the Christological and dogmatic carrying capacity of this kind of expressions was the main purpose of their use by the authors. Rather, it was about the rhetorical attractiveness of their paradoxical character.